2022
DOI: 10.3389/fpubh.2022.1033473
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of COVID-19 booster shot among healthcare workers: A mediation analysis approach

Abstract: Since the thrust of previous research investigations has been on people's willingness to get immunized against the COVID-19 infection, the underpinning principle of compliance has received very little attention. Addressing the possible drivers and mechanisms influencing vaccine acceptance may provide significant insights for limiting the pandemic. In response, we intend to investigate the influence of decision regret and the consequences of post-vaccination adverse effects on the inclination to undertake boost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…In our investigation, pregnant participants appeared to be more impacted by social factors including education and income level, along with misleading facts from social networks than other groups that were susceptible to the vaccination against COVID-19 infection. In line with other research done in various regions ( 45 , 46 ), our research demonstrated that poorer educational and income levels were significant predictors of vaccine hesitancy ( 47 , 48 ). Contrary to other findings on vaccination, this association suggests that people with higher levels of education and income are more concerned about the efficacy and safety of vaccines ( 49 , 50 ).…”
Section: Discussionsupporting
confidence: 92%
“…In our investigation, pregnant participants appeared to be more impacted by social factors including education and income level, along with misleading facts from social networks than other groups that were susceptible to the vaccination against COVID-19 infection. In line with other research done in various regions ( 45 , 46 ), our research demonstrated that poorer educational and income levels were significant predictors of vaccine hesitancy ( 47 , 48 ). Contrary to other findings on vaccination, this association suggests that people with higher levels of education and income are more concerned about the efficacy and safety of vaccines ( 49 , 50 ).…”
Section: Discussionsupporting
confidence: 92%
“…However, instances of individuals succumbing to serious reactions following the COVID-19 vaccine, though rare, were also known. The awareness and fear of the potential risk of death associated with the COVID-19 vaccine could pose a strong disincentive, or more likely lead to regretting the decision to get vaccinated in the first place; this regret might influence the choice to take the optional second booster dose [ 29 ], possibly underlying our finding that there is an association between vaccine-related deaths among close contact/family members and vaccine booster hesitancy.…”
Section: Discussionmentioning
confidence: 99%
“…Social isolation, unfortunately, adversely affects children's psychological health 4 . The most reliable way to dramatically lessen the effects of COVID-19 infection and let kids resume their usual lives is through vaccination 5 , 6 . Both adequate vaccine production and substantial levels of acceptability are necessary for an immunization procedure to be efficacious.…”
Section: Introductionmentioning
confidence: 99%